Estudio de prefactibilidad para la instalación de una planta productora de bisutería bañada en oro y plata en Lima Metropolitana - Gutierrez Jacinto, Diana Graciela (2022)
This research studies the feasibility of installing a plant to produce gold- and silver-plated copper imitation jewelry in Metropolitan Lima in order to commercialize through a virtual platform. The imitation jewelry collection consists of a necklace with a pair of earrings, both gold and silver plated, inside a cream-colored cardboard box with a velvet bag and a cotton flannel. In addition, through a survey and interviews with experts in the field, the product's target audience is women in Metropolitan Lima between the ages of 18 and 55 belonging to the B socioeconomic level. Likewise, to determine the best option to locate the production plant, the factor ranking method and the consistency matrix were used, resulting in a final location in the district of Los Olivos with a requirement of 224 m2 for the premises. On the other hand, the factors related to the market, productive resources, technology, and break-even point were analyzed, concluding that the selection of the plant size is restricted by the market of 6906 units per year. The estimated investment for the project amounts to S/. 263 787,15, which includes the investment in tangible and intangible assets and working capital. Thirty percent will be financed with Scotiabank at an annual rate of 16,08% and the remainder will be financed with equity. Finally, the NPV and IRR were analyzed both economically and financially with an opportunity cost of 20,72% along with financial and social indicators to determine the feasibility of the research.